3D confined assembly of polymer-tethered gold nanoparticles into size-segregated structures. (12th December 2018) - Yang, Yi; Wang, Yulan; Jin, Seon-Mi; Xu, Jiangping; Hou, Zaiyan; Ren, Jingli; Wang, Ke; Lee, Eunji; Zhang, Lianbin; Zhang, Yufeng; Zhu, Jintao
Abstract : A mixture of binary polystyrene (PS)-tethered gold nanoparticles (GNPs) with different sizes can co-assemble into size-segregated core–shell structures under 3D confinement. The location and arrangement of GNPs can be effectively tuned by varying the chain length of the modified PS. Abstract : We demonstrate co-assembly of polystyrene (PS)-tethered gold nanoparticles (GNPs) with different sizes under 3D confinement. Interestingly, core–shell assemblies with particle size segregation were obtained, and the location/arrangement of GNPs can be effectively tuned by tailoring the chain length of the PS ligands. Typically, short PS-tethered GNPs locate in the outer layers while long PS-tethered GNPs accumulate in the interior because of the hydrophilicity difference between them. Binary GNP-based core–shell structures were clearly confirmed by transmission electron microscopy tomography and the formation mechanism was intensively explored. This fabrication approach is applicable to NPs with different sizes, shapes and types. Moreover, both UV-vis absorption spectra and photothermal conversion efficiencies of the GNP assemblies can be effectively regulated by adjusting the PS chain length and content ratio, thus facilitating their biomedical applications in osteosarcoma therapy.